Peperomia campylotropa A.W. Hill: Ethnobotanical, Phytochemical, and Metabolomic Profile Related to Its Gastroprotective Activity - Yazmín K. Márquez-Flores; Jesús Ayala-Velasco; José Correa-Basurto; Alan Estrada-Pérez; M. Estela Meléndez-Camargo (Molecules)
Peperomia campylotropa (Piperaceae) is a species with a traditional Mexican gastroprotective use that has never-before been studied using metabolomics. This study explores the ethnobotanical use of the species, aiming to define the gastroprotective effect of the aqueous extract and characterize its secondary metabolites by UHPLC–MS analysis. To validate its use, we botanically identified the species re-collected in the Municipality of Buenavista de Cuéllar, Guerrero, Mexico. We conducted interviews to provide evidence of the traditional details of its consumption and knowledge. Subsequently, qualitative phytochemical tests were performed to elucidate the possible secondary metabolites, which were also characterized under UHPLC–MS analysis and analyzed according to their primary type and retention times. Indomethacin (IND)- and ethanol (EtOH)-induced gastric damage models in Wistar rats were used for pharmacological evaluation, considering the ulceration index and gastroprotection percentage. Along with the participation in the mechanism of action of nitric oxide (NO), sulfhydryl (-SH) groups and prostaglandins (PG) were elucidated by Wistar rats pretreated with N(ω)-nitro-L-arginine methyl ester (L-NAME), N-Ethylmaleimide (NEM), and IND, respectively. Acute intragastric toxicity was also estimated in NIH female mice. Ninety people were interviewed, revealing the traditional knowledge of P. campylotropa as food and medicine for stomach diseases, including irritation and indigestion. The presence of phenolic compounds (48%), N-containing compounds (22%), glycosides (21%), terpenoids (7%), and lactones (4%) were verified by preliminary phytochemical analysis and by UHPLC–MS in which 162 secondary metabolites were characterized. Besides that, the aqueous extract at 62.5, 125, and 250 mg/kg of body weight (b.w.) decreased the ulcerative index, showing gastroprotection percentages between 60 and 80%, similar to that of omeprazole. Furthermore, -SH group participation in its activity was established. All this evidence supports the gastroprotective activity of P. campylotropa for the first time and contributes to understanding its secondary metabolite content.